Phospholipase C Involvement in Activation of the Muscarinic Receptor-Operated Cationic Current in Guinea Pig Ileal Smooth Muscle Cells - Hiroyuki Okamoto; Toshihiro Unno; Daisuke Arima; Maki Suzuki; Hai-Dun Yan; Hayato Matsuyama; Masakazu Nishimura; Seiichi Komori (Elsevier, 2004)
In guinea pig single ileal smooth muscle cells held under voltage-clamp, the role of phospholipase C (PLC) in activation of the muscarinic receptor-operated cationic current (Icat) was studied. U73122, a PLC inhibitor, prevented the generation of Icat by the muscarinic agonist carbachol. The effect did not involve muscarinic receptor block since it also blocked Icat which was evoked by GTPγS applied intracellularly to activate G proteins bypassing muscarinic receptors. Also, neither cationic channel block nor other possible nonspecific actions seemed to be involved since its analogue (U73343), structurally close but deficient of the PLC-inhibiting activity, did not significantly affect carbachol- or GTPγS-evoked Icat. Antibodies against the α subunits of Gq/G11 proteins (Gαq/Gα11-antibody) blocked only the small component of carbachol-evoked Icat, which was associated with an increase in [Ca2+]i linked to an increase in Gq/11 protein-regulated PLC activity. 1-Oleoyl-2-acetyl-sn-glycerol (OAG), an analogue of diacylglycerol (DAG) produced via PLC-catalyzed metabolism, produced no or only a small current by itself, with the carbachol-evoked Icat remaining unchanged. These results provide evidence for the importance of PLC in Icat generation, and they also strongly suggest that the activity of PLC involved in the primary activation of Icat is neither under regulation by Gq/11 proteins nor dependent on the action of DAG. Keywords:: muscarinic receptor, nonselective cationic current, phospholipase C, diacylgrycerol, smooth muscle